Parallel and Precise Macroscopic Supramolecular Assembly through Prolonged Marangoni Motion. Issue 43 (1st October 2018) - Cheng, Mengjiao; Zhu, Guiqiang; Li, Lin; Zhang, Shu; Zhang, Dequn; Kuehne, Alexander J. C.; Shi, Feng
Abstract: Macroscopic supramolecular assembly (MSA) is a rising concept in supramolecular science, in which building blocks with sizes exceeding 10 μm self‐assemble into larger structures. MSA faces the challenge of developing appropriate self‐propulsion strategies to improve the motility of the macroscopic building blocks. Although the Marangoni effect is an ideal driving force with random motion paths, excessive aggregation of the surfactant and fast decay of motion remain challenging problems. Hence, a molecular interference strategy to drive the self‐assembly over longer times by finely controlling the interfacial adsorption of surfactants using dynamic equilibria is proposed. Surfactant depletion through molecular recognition in the solution to oppose fast interfacial aggregation efficiently facilitates macroscopic motion and assembly. The resulting motility lifetime is extended remarkably from 120 s to 2200 s; with the improved kinetic energy, the assembly probability increases from 20 % to 100 %. Abstract : Go with the Marangoni flow : Through a dissipative network mediated by several molecular equilibria of surfactants, the lifetime and motility of macroscopic building blocks propelled by the Marangoni effect have been prolonged. This molecular interference strategy has improved the efficiency and probability of macroscopic supramolecular assembly, thus mimicking molecular self‐organization on a macroscopic scale.